Female CYBB Mutation Mosaicism Leading to Inheritance of X-linked Chronic Granulomatous Disease - ZHANG Yue; SHU Zhou; LI Yan; PIAO Yurong; HAN Tongxin; MAO Huawei (罕见病研究, 2022)
Chronic granulomatous disease (CGD) is a heterogeneous primary immunodeficiency characterized by severe bacterial and fungal infections and tissue granuloma formation early in life. Diagnosis of CGD involves the granulocyte function assays and gene mutation analysis. X-linked CGD (XL-CGD) caused by gene defects of CYBB is the most prevalent type of CGD. The clinical data and gene characteristics of a rare female X-chromosome mosaicism leading to inheritance of XL-CGD were reported here. The patient is a 7-year-old boy manifested as recurrent lower respiratory tract infection and failed to thrive. The patient had a history of osteo- myelitis and perianal abscess, with Bacille Calmette-Guérin (BCG) vaccine complications. Respiratory burst of neutrophils was measured with DHR oxidation assay and the histogram showing no significant change in neutrophil fluorescence after stimulation of the patient and the mother's histogram had a pattern of 2 peaks after stimulation. A heterozygous mutation in the CYBB gene (c.866G > A, p.W289X) was identified through inheritance from the patient's mother. Genetic analysis from blood and cheek mucosal cells indicated the female was a mosaicism in CYBB with mutation was present in about 19.5% of her leukocytes. We reported the clinical data and gene characteristics of a rare female X-chromosome mosaicism leading to inheritance of XL-CGD for the first time in China to enrich the understanding of XL-CGD and provide new sights for the hereditary counseling.